131 Milk yield of ewes fed with diets of different energy levels. (29th July 2019) - Gallo, Sarita Bonagurio; Junior, Vanderlei Benetel; Santos, Fernanda Ferreira dos; de Oliveira, Mariluce Cardoso; Tedeschi, Luis Orlindo
Abstract: An adequate sheep milk production ensures survival and optimum lamb's growth and development through the weaning. To evaluate the effects of different energy sources in the diet of ewes on their milk yield, an experiment was carried out at the Faculty of Animal Science and Food Engineering of USP, Brazil, using 56 pregnant ewes, Dorper and Santa Ines breeds, average live weight of 70 kg, randomly distributed in four treatments: control group (fed according to the 2007 NRC recommendation); and groups with 10% more energy with different sources (starch, ST; protected fat, PF; and chromium, Cr). Dry matter intake was approximately 3% of the live weight of the ewes, to all treatments, but the control group with intake of 2.1 Mcal EM/d and the other with 2.3 Mcal EM/d. Ewes were fed the experimental diets at the beginning (50 d) and end of the gestation (50 d). In the middle of the gestation (50 d) the sheep were fed according to the recommendation of the NRC (2007). At 20, 30, 40, 50, and 60 days post-lambing, the milk yield was assessed using an indirect method of double weighing the lambs (one weight before suckling, another weight after suckling). The ewe milk yield was analyzed using contrasts and statistical significance at 5% of probability. There was no statistical difference (P > 0.05) among the diets evaluated on milk yield of the ewe (0.42, 0.45, 0.38, 0.3, and 0.14 kg/d for 20, 30, 40, 50, and 60 days of lactation). We concluded that milk yield of ewes receiving different levels and source of dietary energy did not differ. Additionally, the use of Cr or protected fat did not influence milk yield when added at 10% of the required energy for lactation. Acknowledgment to FAPESP (process 2017/20555–8).